AH1N1 virus infection in obstetrics - Piekut, Krystyna; Foremska, Daria; Kulesza-Brończyk, Bożena; Chlewicka, Julita; Terlikowski, Sławomir (Nursing Problems / Problemy Pielęgniarstwa, 2013)
Influenza is a viral infectious disease of the respiratory system. It is caused by a virus AH1N1v and has more severe and rapid progress than the seasonal flu. The symptoms of infection are similar to those of a seasonal flu but quickly develop severe complications such as pneumonia, ARDS (Acute Respiratory Distress Syndrome) and septic shock. Rapid increase in the number of cases in 2009 called out the announcement of a pandemic caused by a virus AH1N1v. There were cases of infection among pregnant women who are at greater risk as well as children and the elderly. AH1N1 virus infection in pregnant women deserves special attention due to the fact of endangering the life and health of not only the mother but also the foetus with an increased risk of miscarriage and premature birth. The basis of prevention is vaccination with monovalent inactivated vaccine. It is also recommended for pregnant women. The aim of this study was to present specificity of preventive and therapeutic and nursing care to a pregnant woman infected with influenza AH1N1.